Awareness about covid-19 in Bachelor of Dental Medicine Students in Baiturrahmah Padang - Sri P. Utami; Intan BE. Mahata; Hiranti S. Harien (Journal of Dentomaxillofacial Science, 2021)
Objective: The aim is to find out awareness about COVID-19 among undergraduate dentistry students at the Baiturrahmah Faculty of Dentistry, Padang. Material and Methods: When the research was carried out in September 2020.The method of data analysis in this study used the SPSS program with univariate and bivariate analysis. The processed data is presented in table form. Results: That as many as 99.4% of respondents had good knowledge awareness about Covid-19, 0.6% awareness of bad knowledge, 97.7% of respondents got the first information about Covid-19 through the media, 56% of respondents got the latest Covid information via the internet, only 11.4% of respondents are taking Covid-19 courses, and 5.1% are still taking courses until now. Conclusion: The target population of this study were undergraduate dentistry students force 2017, 2018, and 2019 with a sample of 175 people. This research was conducted online in the city of Padang using google form media for distributing questionnaires.